Monitoring System for Student Internships Using the Rapid Application Development (RAD) Method - Kaban, Roberto; Sembiring, David JM; Br Tarigan, Ita Margaretta (Cattleya Darmaya Fortuna, 2023)
This research aims to develop a system that facilitates monitoring activities of students undergoing internships, with a case study on student internship activities at the Indonesian Institute of Technology and Business (ITB Indonesia). The system development method used is Rapid Application Development (RAD), with four structured and interdependent stages in each phase, namely Requirements planning, User Design, Construction, and Cutover. The outcome of this research is a web-based system with a responsive interface across all devices (smartphones, tablets, and laptops). The system includes features for student location-based attendance, student activity reporting at internship sites, student guidance processes with supervising mentors, as well as monitoring the guidance process of students and supervising mentors conducted by the head of the study program.